Exploring Abul Hasan ʽAli Nadwi's views on distinctive features of Islamic civilization - Mohammad, Saud; Abdul Rahim, Adibah (International Islamic University Chittagong, Bangladesh, 2022)
The seventh to thirteenth centuries was a very glorious period of Islamic civilization. during this time, the Islamic world advanced in the arts and sciences and influenced other segments of the world. Unfortunately, due to the rise of Arab imperialism, Islamic civilization experienced many ups and down, but the remarkable decline was noticed after Western dominance over the Muslim world started to increase a few centuries ago. Under the influence of Western civilization, the Muslim world began to regress towards backwardness. As a matter of fact, Muslims all over the world are in decline, and in order to retain their lofty status, Nadwi suggested reviving Islamic civilization as an alternative to Western civilization. He criticized Western civilization for its moral degradation and lack of spirituality. This paper, therefore, will explore Nadwi's views on the most distinctive features of Islamic civilization in comparison to Western civilization. Nadwi strongly believed that Islamic civilization should be the pillar of world civilization that can guide humankind toward the right path in this world and otherworldly life.